SUBSTANTIATION OF THE PALEOCENE-EOCENE BOUNDARY IN WESTERN SIBERIA BY FORAMINIFERS - Podobina V.M. (My University, 1998)
Data on stratigraphy and foraminifers from the Paleocene and Eocene deposits in western Siberia are correlated and the boundaries between the two series are verified. New results for boreholes 1, 2, 3, and 4 on the Kaimysov arch (the Central region) are presented. Judging from the microfauna composition, especially from that of endemic agglutinated siliceous foraminifers and from peculiar features of sedimentation, the West Siberian province is assumed to represent the southern margin of the biogeographic Arctic Circumpolar Realm of the discussed epochs. The benthonic calcareous and planktonic foraminifers occasionally encountered in the province were correlated with similar Paleocene and Eocene forms, among them those from stratotypes of Denmark, Belgium, and England. The Danian (the Brotzenella praeacuta Zone of the Lower Paleocene) of western Siberia is established in the upper layers of the Gan'kino Formation containing benthonic and planktonic foraminifers. The lower half of the Talitza Formation, within which the Aminoscalaria friabilis Zone has been distinguished, is referred to the Zealandian. In the Transurals region, this part of the formation corresponds to the Cibicidoides proprius Beds, many species of which are encountered in appropriate deposits of the Zealand Island stratotype and southern Sweden. The Thanetian Cibicidoides favorabilis Zone is recognized on the basis of planktonic foraminifers found in the Turgai depression, along with its zonal species, and the unit is correlated with that of the Thanet Island stratotype (England). The Ypresian (Lower Eocene) is established in western Siberia on the basis of calcareous benthonic and planktonic foraminifers. The Anomalinoides ypresiensis Zone, similar to the synonymous zone of the Ypresian in the Netherlands, is distinguished for the first time in this part of the section. The zone is confidently defined in sections of boreholes 1 and 2 of the Kaimysov arch. In addition to benthonic forms, Planorhotalites species typical of the Ypresian are found. The boundary between the Paleocene and Eocene is distinguished between the Thanetian Cibicidoides favorabilis and Ypresian Anomalinoides ypresiensis zones of western Siberia. The figure presented shows the correlation of the Paleocene and Eocene zones (boreholes 1, 2, 3, and 4) within the Kaimysov arch. Two micropaleontological plates are presented as well.
Keywords: Paleocene; Eocene; Кайнозой::Палеоген::Палеоцен; Cenozoic::Paleogene::Eocene; Cenozoic::Paleogene::Paleocene; Кайнозой::Палеоген::Эоцен